Developing Students’ Aesthetic and Artistic Perception through Digital Methods - Usmonov Umid Farxodovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: The use of digital methods in art education provides innovative opportunities for developing students’ aesthetic sensitivity and artistic perception. By integrating multimedia tools, interactive applications, and digital design platforms, educators can create immersive learning experiences that engage students in visual exploration and creative expression. This study examines the effectiveness of digital technologies in fostering artistic skills, enhancing aesthetic awareness, and promoting critical appreciation of visual art among secondary school students. Additionally, the research highlights pedagogical strategies, practical applications, and challenges associated with implementing digital methods in art classrooms.